Conservation of a Critically Endangered Endemic Halophyte of West Portugal: A Microcosm Assay to Assess the Potential of Soil Technology for Species Reintroduction - Cortinhas, Ana; Ferreira, Teresa Cardoso; Abreu, Maria Manuela; Caperta, Ana D. (Frontiers in Ecology and Evolution, 2021)
The soil system was frequently overlooked during plant reintroduction planning and practice since working with soils and plant roots can be difficult, particularly in saline environments. Coastal saline environments are major contributors to regional and global biodiversity and an important source of endemic species. However, various species are in decline or considered threatened, particularly halophytes (salt tolerant) due to negative anthropic impacts. The Lusitanian endemism halophyte Limonium daveaui had a large distribution range along the west coast of Portugal but currently it shows a restricted distribution in the Tagus estuary. Field prospections revealed that this critically endangered species forms few population nuclei with small size invaded by exotic species. In this study, we investigated the potential utilization of Technosols an innovative sustainable, ecological engineering method combined with brackish water irrigation for potential L. daveaui reintroduction in native habitats. Seed germination percentages were evaluated in distinct environmental conditions. Through a microcosm assay, a Technosol was constructed using a saline Fluvisol with a mixture of low value inorganic and organic wastes, which were chemically characterized. Plants were cultivated in the Fluvisol and Technosol and irrigated with brackish water collected in the nearby area. To assess plant growth, morphometric parameters and plants’ physiological status were assessed and the fresh and dry biomass determined. Results showed that seed germination was higher in moist filter paper with distilled water than in Fluvisol or Technosol. Plants grown in Technosol had a greater development, with higher values of photosynthetic indexes and biomass production than in Fluvisol. Our findings provide a basis for future in situ conservation studies and support that eco-friendly soil technology approaches are beneficial to conserve rare halophyte species.